2011
DOI: 10.1007/s12110-011-9112-x
|View full text |Cite
|
Sign up to set email alerts
|

The Place of Proximity

Abstract: The mother-adult daughter relationship has been highlighted in both the social sciences and the public health literature as an important facet of social support networks, particularly as they pertain to maternal and child health. Evolutionary anthropologists also have shown positive associations between support from maternal grandmothers and various outcomes related to reproductive success; however, many of these studies rely on proximity as a surrogate measure of support. Here I present data from the Puerto R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 65 publications
2
26
0
Order By: Relevance
“…This suggests that when in-laws live nearby, but do not have much contact nor provide help, their presence actually reduces fertility outcomes. A similar result was found in Puerto Rico, where women who lived geographically close to their mothers, but did not receive support from them actually had increased odds of infant death and low birth weight offspring (Scelza 2011). For women who have geographically close kin, but have poor relationships with them, their fertility may actually be reduced.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This suggests that when in-laws live nearby, but do not have much contact nor provide help, their presence actually reduces fertility outcomes. A similar result was found in Puerto Rico, where women who lived geographically close to their mothers, but did not receive support from them actually had increased odds of infant death and low birth weight offspring (Scelza 2011). For women who have geographically close kin, but have poor relationships with them, their fertility may actually be reduced.…”
Section: Discussionsupporting
confidence: 65%
“…Kin may also provide other types of non-physical help, such as emotional support, informational help, or emergency support. Research has shown that social support is important for good health and well-being (Berkman 1984;Sosa et al 1980), and we might expect that social or emotional support has an effect on fertility, potentially through the decision to have more children, or because pregnancies are more likely to result in live births and healthy children (Scelza 2011). Informational help may include the information kin provide about how best to raise children or when to seek medical care.…”
Section: Hypothesized Causal Pathway Of Kin Influencementioning
confidence: 99%
“…Thus, Mattison (2011) explores the explanatory value of a simple quantitative model of matriliny , emphasizing that the forms of wealth affecting reproduction may be more important in determining whether inheritance or wealth transmission will be daughter-biased than paternity certainty is on its own. Scelza (2011) shows that geographic proximity may not always be a good indicator of maternal support in studies of collaborative child-rearing, highlighting the dynamics between proximity and reported direct support in determining outcomes of child well-being. Both of these studies elucidate theoretical causality in kinship behavior by contemporaneously weighing two or more putative causes through multivariate analysis.…”
Section: Quantitative Approaches To Kinshipmentioning
confidence: 99%
“…For example, in the Gambia, Noel-Miller (2005:199) found that the coresidence of a grandparent and grandchild did not improve the grandchild's survival chances. In Puerto Rico, Scelza (2011) concluded that geographic proximity between a woman and her mother was crucial for infant health-but only so long as it occurred in conjunction with the mother's social support.…”
Section: Proximity Hypothesismentioning
confidence: 99%